From cannabis to problem drinking? Use and abuse from youth to adulthood. Issue 1 (February 2015) - Hyggen, Christer; Hammer, Torild
Aims: The transition from youth to adulthood is associated with changes in the consumption of drugs and alcohol. The aim is to explore the process of "maturing out" of high levels of alcohol consumption, substance use and alcohol related problems from youth to adulthood. We are particularly interested in the relationship between the use of cannabis and alcohol consumption in relation to indicators of adult roles and responsibilities and alcohol-related problems over the life-course. Methods: We used data from the norwegian longitudinal panel survey Arbeid, Livsstil og Helse (ALH). The data contains information on alcohol and drug consumption, alcohol related problems and a range of indicators of adulthood like marriage and parenthood from surveys repeated in 1985, 1987, 1989, 1993, 2003 and 2010. The sample was nationally representative for the cohorts born 1965–1968 and thus contains individual histories from youth (17–20 years) to adulthood (42–45 years) with response rates ranging from 80% in 1985 to 53% in 2010 (total n=1997). Results: Alcohol consumption is found to be substantially higher among users of cannabis than among nonusers throughout the period from youth to adulthood. The use of cannabis, the level of alcohol consumption and probability of experiencing alcohol related problems decrease as the cohorts grow older. Alcohol related problems are still associated with the level of involvement with cannabis: those with a current or previous involvement with cannabis report more alcohol related problems. Taking into account the decreasing trend of alcohol related problems with age we find that becoming a parent and/ or getting married reduces the risk of experiencing such problems.